UPAYA PEMERINTAH MENGELOLA TEKANAN PUBLIK: ANALISIS RESPON PEMERINTAH ATAS TUNTUTAN 17+8 PASCA DEMONSTRASI AGUSTUS 2025 - Sulistiawati, Henny; Afrilia, Merina (Program Studi Ilmu Pemerintahan FISIP Universitas Galuh, 2026)
Public pressure is an inherent feature of modern democratic governance and represents a managerial challenge for state institutions. This article analyzes the public management responses of the government and the House of Representatives (DPR) to the 17+8 demands following the major demonstrations of August 2025 in Indonesia. The study employs a qualitative approach with a document-based case study design, drawing on demand documents, official government and parliamentary statements, and national media reports. The findings reveal three main patterns of state response: communication response, policy response, and coordinative response. Communication responses dominated the initial phase, aiming to maintain stability and legitimacy, yet tended to be normative and defensive. Policy responses were selective and short-term, reflecting crisis management rather than structural reform. Meanwhile, coordinative responses remained ad hoc and lacked institutional consolidation. Analysis through the lenses of public responsiveness, accountability, and policy management indicates that the state was procedurally responsive in the early phase, but not yet optimal in integrating public pressure into a coherent and sustainable policy management cycle. Theoretically, this study contributes to public management scholarship by positioning public demonstrations as managerial challenges within democratic governance. Practically, it offers insights for policymakers to design more integrated, substantive, and sustainable responses to public pressure.